Roads to Resilience: Building Dynamic Approaches to Risk to Achieve Future Success - Goffin, Keith; Hopkin, Paul; Szwejczewski, Marek; Kutsch, Elmar (Cranfield University, 2014)
In complex and constantly changing business environments with ever more complex risk, one of the key questions that boards ask of themselves is: “What can we do to future-proof ourselves against the growing array of risks?” In a search to answer this question, case study based research, undertaken by Cranfield School of Management on behalf of Airmic, looked at eight leading companies that constantly have to deal with significant uncertainty and risk and yet have survived, maintaining both their reputation and balance sheet. The ways they approach risk management and have achieved resilience was investigated at: AIG, Drax Power, InterContinental Hotels Group, Jaguar Land Rover, Olympic Delivery Authority, The Technology Partnership, Virgin Atlantic and Zurich Insurance.
ISBN: 978-0-9928275-0-2